Interference of Bilirubin in Creatinine Value Measurement by Jaffe Kinetic Method - Chaudhary, Siddhartha Shankar; Shah, Jay Prakash; Mahato, Ram Vinod (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
BACKGROUND: Creatinine measurement in icteric sample is a major but unresolved problem. Bilirubin causes negative interference in creatinine value measurement using general techniques. The objective of this study was to find differences in creatinine value by Jaffe Kinetic method pre-incubation and without pre-incubation with NaOH. METHODS: This was a cross sectional, descriptive study carried out in 71 samples with different level of bilirubin concentration. We took blood samples of 71 different patients, 48 males and 23 females, from two different hospitals of Kathmandu village. Both creatinine and bilirubin concentration in serum samples were measured by using Staxfax 3300 semi auto analyzer in the hospital. In the laboratory creatinine value was measured by kinetic method and bilirubin measured by Jendrassik/ Grof method using commercial kits. Statistical analysis of quantitative data was done by using SPSS version 16.0. RESULTS: The results shows differences in creatinine values with respect to methods and extent of bilirubin concentration. It was found that the creatinine obtained by pre-incubation with NaOH has greater value than without pre-incubation (i.e. by direct estimation using working reagent). It was also shown that the high bilirubin cause the interference in greater extent. The significant interference was seen in the sample with bilirubin concentration greater than 20 mg/dl i.e. creatinine value after treatment with NaOH prior to dispensing picric acid is significantly increases, P<0.01 at 99% confidence level. CONCLUSION: This shows that the bilirubin has negative interference in creatinine value measurement by ordinary laboratory practices and interference increases with higher concentration of bilirubin in blood sample. DOI: http://dx.doi.org/10.3126/acclm.v1i1.12311 Ann. Clin. Chem. & Lab. Med. 1(1) 2015: 25-28